2009
DOI: 10.1016/s1726-4901(09)70421-6
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Predicting Risk of Serious Bacterial Infection in Febrile Infants Younger Than 3 Months of Age

Abstract: These findings suggest that sex, serum CRP concentration and spun urine WBC count can be used to accurately predict SBI in febrile infants aged less than 3 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A causal relationship between neonatal jaundice and certain bacterial infections has been noticed, including urinary tract infections (UTIs) [ 4 5 ]. It was suggested that some Gram-negative bacteria can excrete some toxins called hemolysins that can destroy the red blood cells of the newborn and lead to unconjugated hyperbilirubinemia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A causal relationship between neonatal jaundice and certain bacterial infections has been noticed, including urinary tract infections (UTIs) [ 4 5 ]. It was suggested that some Gram-negative bacteria can excrete some toxins called hemolysins that can destroy the red blood cells of the newborn and lead to unconjugated hyperbilirubinemia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…1e3 Although it is mostly benign, some cases may have the possibility of having other diseases in combination. 4 There have been some reports regarding the relationship of idiopathic hyperbilirubinemia and bacterial infections, 5 such as urinary tract infection (UTI). 6 However, it is still not recommended to perform routine urinary tests in jaundiced infants for such infections.…”
Section: Introductionmentioning
confidence: 99%
“…These findings imply that male gender is a risk factor for the development of SBI in infants up to 90 days old. Other authors suggest a similar conclusion 1,22,[25][26][27] , so it is important to take gender into consideration during the evaluation of febrile infants. Although most studies found no link between gender and SBI 10,12,20,[28][29][30][31] , that discrepancy should be considered from the epidemiological and population point of view.…”
Section: Discussionmentioning
confidence: 65%